Character Value Content in Learning Short Story Texts In Senior High School - Devian Aghna Perdana Ababil; Laili Etika Rahmawati (Ikaprobsi, 2023)
Character education is currently a major topic in education. To improve education, we must uphold the standards of character education. Many moral principles that form the basis of character development can be learned from short stories and used in teaching in the classroom. The purpose of this study was to analyze the value content of character education in Indonesian language learning on short story text material for class XI at SMA Batik 2 Surakarta. This type of research is qualitative research. The subjects in this study were Indonesian language teachers at Batik 2 Surakarta High School and class XI students at Batik 2 Surakarta High School. Sources of data in this study were obtained through observation, interviews and documentation. The results of this study, namely 1. There are 12 values ​​of character education in learning short story texts, including religious, honest, tolerance, discipline, creative, independent, curiosity, national spirit, communicative, fond of reading, love peace, responsibility, 2. The value of character education is contained in the RPP document contained in several components in the RPP, namely, Core Competence (KI) and steps for learning activities, 3. Learning short story texts has implemented character values ​​well. This can be proven by the number of students who achieve the Minimum Completeness Criteria (KKM)